(untitled) (Research, Society and Development, 2021)
Rainfall erosivity, defined as the potential of this in causing soil erosion, is a function only of the physical characteristics of the rain itself, ie its amount, intensity, drop diameter, terminal velocity and kinetic energy. Aims to evaluate the erosivity index (EI30) from rainfall variability distributed in the basin of the Upper River Paraiba Course - PB/Brazil, considering the number of higher rainfall than 57 years of data for the 12 municipalities that make up the study area. To determine the erosivity factor was used the equation proposed by Wischmeier (1971) and Wischmeier and Smith (1958, 1978), the R factor, rainfall erosivity is the sum of the monthly values ​​of erosivity. The results showed no significant correlations to the Barra de São Miguel municipalities, Camalaú, Monteiro, Silver, São João do Tigre, San Jose of the Lambs and São Sebastião do Umbuzeiro, while for the municipalities of Cabaceira, Caraúbas, Congo and Sierra White were identified moderate erosion rates to weak in a few months the wettest quarter of the region.